A new species of Brachionidium (Pleurothallinidae) from the Yanachaga Chemillen National Park, Pasco, Peru - Valenzuela Gamarra, Luis
A new Brachionidium from Peru is described and illustrated. The new species, B. montieliae,was discovered in one of the highest mountains of the Oxapampa-Ashaninka-Yanesha Biosphere Reserve (BIOAY), situated above the forests of the humid puna of the Yanachaga Chemillen National Park at 3590 m in elevation. It is similar to Brachionidium vasquezii but differs in the oblong-elliptic, denticulate, and semi-erect leaves, somewhat lanuginose abaxially; the purple lanuginose adaxially and papular abaxially, entire, acuminate lateral sepals; the purplish oblong-ovate dorsal sepal, lanuginose on the adaxial surface, papular abaxially; the purple petals with scalloped edges, acuminate to obtuse apex ending in a thin, slightly abbreviated tail; the lip with apiculate lateral angles and with a central, trapezoid verrucose callus on the disc. Brachionidium montieliae is a terrestrial species that thrives in the humid Puna forests at elevations around 3400-3600 meters. The ecosystem is characterized by a sclerophyllous forest with a diverse range of tree species. Information on distribution, ecology, etymology, and phenology is also included. There are potential threats from annual burning practices in the region. Given the potential risks, it is imperative to undertake immediate conservation measures and promote environmental awareness to safeguard this species.